Trends in annual rainfall amounts at Jeddah and Al-Wajh stations in the Kingdom of Saudi Arabia for the years (1987-2016 AD) - Alanazy, Jamila Awadh (Journal of natural sciences, life and applied sciences, 2023)
In this study, the researcher aims to analyze the trend of annual rainfall in the Kingdom of Saudi Arabia for the period (1987-2016 AD), relying on the data available for the Jeddah and Al-Wajh stations, adopting mathematical equations that use moving averages for five years, as well as adopting midterm averages, based on the nature of the relationship The simple linearity that often appears between annual rainfall amounts and time.To come up with accurate results, the researcher used statistical methods to show all midterms, correlation coefficients (r) and regression (b) based on standard error (S.E.), student (t) test, and interpretation coefficient (r²). and a significance level of 5%. The results of each of the moving averages and midterms showed that the amounts of precipitation are decreasing in the two stations of Jeddah and Al-Wajh, despite the big difference in the amount of decrease in the two stations. Al-Wajh station showed an increase in the direction of rain, as it was found through the application of the statistical examination that these trends are not important, whether by increase or decrease, and that there is no clear and certain trend for the amounts of rain in the future, but rather the results confirm the nature of the random and irregular rains known for the rains of the desert climatic systems.
Keywords: Annual rainfall; moving averages; midterm averages; simple linear regression relationship; statistical significance; statistical examination; Saudi Arabia; Jeddah; Al Wajh